How does willingness and ability to pay of palm oil smallholders affect their willingness to participate in Indonesian sustainable palm oil certification? Empirical evidence from North Sumatra - Aisyah Dinda Dewi (De Gruyter, 2021)
A sample survey of palm oil smallholders was used to examine the amount of Willingness and Ability to Pay (WATP) and the factors that determine WATP as well as the impact of WATP on the willingness to participate of smallholders in Indonesian Sustainable Palm Oil (ISPO) certification scheme. Results reveal that the average amount of WATP accounted only half of the certification cost, implying that partial assistance is needed to support the smallholders through government subsidy. The study shows that WATP significantly affects the willingness to participate, and smallholders with higher WATP are more likely willing to participate in ISPO. Both WATP and willingness to participate are significantly determined by social norms (farmers collective impression) and awareness of the consequences of unsustainable farming practices. This result indicates the necessity to improve a positive impression on ISPO and increase awareness of the importance of following the sustainability principles of palm oil farming to increase the smallholders’ WATP, and at the same time their willingness to participate in ISPO program. It is suggested for the government to intensify the campaign of the program to a wider range of smallholders to increase their knowledge and awareness of the certification program.